Genetic markers in glaucoma. Issue 4 (April 1980) - David, R; Jenkins, T
Abstract : A number of genetic polymorphisms have been investigated in Negro and Caucasoid patients with glaucoma and the results compared with data obtained on healthy controls. A sample of 61 Negro patients was not significantly different from a sample of 238 controls with respect to 18 red cell and serum protein systems; no association between glaucoma and any of these systems could be demonstrated. The comparison among Caucasoids, using 14 systems, was made between 31 patients and 70 controls. The populations differed from each other in the rhesus and Duffy blood group systems, and a significant association between open-angle glaucoma and rhesus D (+) was found.